2014
DOI: 10.1111/ggi.12380
|View full text |Cite
|
Sign up to set email alerts
|

Screening for tinea unguium by thermography in older adults with subungual hyperkeratosis

Abstract: Our study suggests that foot temperature can be used to screen for tinea unguium in people with subungual hyperkeratosis. This non-invasive and simple screening method would help clinicians to set priorities in terms of carrying out direct microscopy to diagnose tinea unguium in elderly residents in care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Analysis of the results also shows a relation between the presence of infection and foot temperature in participants aged 18-31 years with asymptomatic or incipient onychomycosis, revealing a lower temperature by almost 2 • C in positive cases of onychomycosis due to dermatophyte fungi, both in men and women, partially agreeing with the findings of Villaseñor-Mora et al (2013) [36] and Miura et al (2014) [39]. The former reported a lower temperature in nails infected by onychomycosis when the causal agent is a dermatophyte fungus in patients aged 30-75 years with type II diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of the results also shows a relation between the presence of infection and foot temperature in participants aged 18-31 years with asymptomatic or incipient onychomycosis, revealing a lower temperature by almost 2 • C in positive cases of onychomycosis due to dermatophyte fungi, both in men and women, partially agreeing with the findings of Villaseñor-Mora et al (2013) [36] and Miura et al (2014) [39]. The former reported a lower temperature in nails infected by onychomycosis when the causal agent is a dermatophyte fungus in patients aged 30-75 years with type II diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…The low prevalence in our study may be the result of studying a young, similarly aged university population with no symptoms. Miura et al (2014) [39] did not report a significant correlation between temperature and age. Our study, however, showed a higher temperature in older participants without infection (25-30 years) by almost 1 • C.…”
Section: Discussionmentioning
confidence: 82%
“…Miura et al 35 evaluated older adults who had subungual hyperkeratosis with and without nail dermatophytosis. They observed that the average temperature of the first toe of patients with onychomycosis was significantly lower (30.2 ± 2.6°C) than the temperature of patients who did not have this condition (32.8 ± 3.2°C, p = 0.001).…”
Section: Irt Imaging In Dermatologymentioning
confidence: 99%
“…In such study, sensitivity was 81.8% and specificity, 65.7%. This makes thermography a fast and practical screening method for identifying onychomycosis in older people 35 …”
Section: Irt Imaging In Dermatologymentioning
confidence: 99%
See 1 more Smart Citation